UM ESTUDO COM OS PROFESSORES DO ENSINO MÉDIO SOBRE A EDUCAÇÃO SEXUAL - Comin, Pamela Cristina; Lise, Fabio Augusto (Seminário de Iniciação Científica e Seminário Integrado de Ensino, Pesquisa e Extensão (SIEPE), 2021)
This article aims to understand the concepts and discourses used by high school teachers in a public school located in the west of Santa Catarina, when talking about Sexual Education, identifying, analyzing and describing the difficulties, understanding the concept and the way it teachers approach and deal with the subject, as well as parents and the school help in this process of informing and guiding. In adolescence, many questions and curiosities begin to arise, whether physical, emotional and social, adolescents look for a place to fit in and a group to belong to, help from school and parents is necessary, when it comes to sex education, it is important emphasize that, in adolescence, many young people start their sexual life often without proper guidance, either for fear of questioning or taboo from people close to talking about it. To perform the data collection, 13 teachers from a public school were interviewed through an online questionnaire, obtaining the necessary information to complete the article. It can be analyzed that although teachers understand the need to talk about sexual education, there is still a portion of teachers who define sexual education as just teaching how to have sex, however, the real definition would be to help, teach and prevent adolescents, showing their responsibilities and consequences of early pregnancy or STD (Sexually Transmitted Diseases). Keywords: Sex education. Teenagers. School.